Green Economy-Based Multi-Objective Optimization Model for Agricultural Supply Chain Network Design Using Lexicographic Method - Febrian, Rizky; Chaerani, Diah; Nahar, Julita (Jurnal Matematika Integratif, 2026)
This Article presents a multi-objective optimization model for agricultural supply chain network design that incorporates green economy principles. The problem is formulated as a Many-to-Many Location Routing Problem (MMLRP) to address strategic decisions including Regional Food Hub site selection, commodity flow allocation between producers and hubs, distribution routing to consumer zones, and warehouse capacity planning. Two objective functions are solved hierarchically using the Lexicographic Method: maximizing demand fulfillment as the primary objective, followed by minimizing total costs comprising shipping, warehousing, and hub construction expenses. The model incorporates flow conservation constraints, capacity limits for producers and demand zones, and logical constraints linking distribution activities to hub establishment. Environmental considerations are integrated through carbon tax components and vehicle emission factors in transportation activities, enabling decision-makers to account for the environmental impact of logistics operations. Results demonstrate that the optimal network configuration identifies strategic hub locations and efficient distribution patterns characterized by short-distance delivery clusters that minimize carbon emissions, while maintaining cross-regional shipments from major production centers to satisfy demand requirements.